Toxicity and repellency effect of some indigenous plant extracts against lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) (Journal of Bio-Science, 2016)
Context: Insect bio assay and repellency test can play a vital role in special environmental conditions.Objectives: To screen out the insecticidal potency of some plant extracts to control the adult lesser grain borer by insect bioassay and repellency tests.Materials and Methods: Toxicity test of five indigenous plant extracts with three concentrations were conducted against Rhizopertha dominica. Insect mortality was recorded at 24, 48, and 72 HAT. For residual toxicity test, insect mortality was recorded at 1, 2, 7, 15 and 21 DAT. The repellent activities were evaluated using the filter paper impregnation method and the data were counted at hourly intervals up to 6th hour. In all cases ten insects per replication were tested and each treatment was replicated thrice. The collected data were statistically analyzed.Results: Among the tested plant extracts, neem showed the highest toxic and repellent effects against the lesser grain borer. All the doses applied had direct toxicity, residual and repellency effects while 8% dose showed the highest response. The order of toxicity was found as neem > biskatali > karabi > akanda > ata. Mortality percentages were directly proportional to the time after treatment.Conclusion: This study proved that the leaf extract of indigenous plants like neem, biskatali, karabi ata and akanda can be used to protect stored grain pests.J. bio-sci. 22: 31-39, 2014